Lupine, a source of new as well as hidden food allergens - Jappe, Uta; Vieths, Stefan (Molecular nutrition & food research, 2010)
The present review summarizes current knowledge about lupine allergy, potential sensitization routes, cross-reactions between lupine and other legumes, and the respective IgE-binding proteins. Since the 1990s, lupine flour is used as a substitute for or additive to other flours, mostly wheat flour, in several countries of the EU. In 1994, the first case of an immediate-type allergy after ingestion of lupine flour-containing pasta was reported. Since then, the number of published incidents following ingestion or inhalation of lupine flour is rising. So far, the Lupinus angustifolius β-conglutin has been designated as the allergen Lup an 1 by the International Union of Immunological Societies Allergen Nomenclature Subcommittee. Initially, publications focussed on the fact that peanut-allergic patients were at risk to develop anaphylaxis to lupine due to cross-reactivity between peanut and lupine. At present, however, the ratio between cases of pre-existing legume allergy (mostly peanut allergy) to de novo sensitization to lupine seed is nearly 1:1. Although in December 2006, lupine and products thereof were included in the EU foodstuff allergen list according to the Commission Directive 2006/142/EC amending Annex IIIA of Directive 2000/13/EC in order to prevent severe reactions caused by “hidden food allergens”, the majority of patients and medical personnel are still not aware of raw lupine seed as potentially dangerous food allergen.